Homicide, gender and responsibility: an international perspective - Fitz-Gibbon, Kate; Walklate, Sandra (Routledge studies in crime and society, 2016)
pt. 1. Making sense of the boundaries between homicide, gender and responsibility -- pt. 2. Blurring the boundaries between homicide, gender and responsibility.